Artificial adaptive systems using auto contractive maps : theory, applications and extensions /: theory, applications and extensions. (2018) - Buscema, Massimo, 1955-; Massini, Giulia; Breda, Marco; Lodwick, Weldon A; Newman, Francis (Francis D.); Asadi-Zeydabadi, Masoud
No abstract available